IMPLEMENTASI METODE ANALYTICAL HIERARCHY PROCESS DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI - Gusta Gunawan (Universitas Bengkulu, 2019)
This study aims to apply the method of Analytical Hierarchy Process (AHP) to prioritize the management of a watershed that can adopt a variety of stakeholder interests to bring into sustainable DAS management model . Priority weighting method using Analytical Hierarchy Process (AHP) developed by Saaty (2008) . Purpose (Goal) is an integrated watershed management that can adopt the interests of various stakeholders . The criteria used are economic, ecological / environmental , and social . Alternative selected are six namely productivity , income, max discharge and min discharge , erosion , and labor . The result of weighting method using AHP have been known that the top priority of the watershed management purpose is to tackle the issue of maximum discharge/flood (0.322) and after that following the issue of productivity (0,239) . Lowest weight in the workforce (0,031) . The amount of weight above reflects the level of interest of the stakeholders involved in watershed management .